INDONESIAN QUALIFICATION FRAMEWORKS: DEVELOPING RESEARCH PERSPECTIVES - Mada Aditia Wardhana; Pudjiati, Pudjiati (Media Bina Ilmiah, 2024)
The Indonesian Qualification Framework (IQF) is a pivotal tool for standardizing qualifications in Indonesia, ensuring that educational outcomes align with the needs of the workforce and industry standards. This study aims to explore the development of research perspectives within the context of the IQF, focusing on its implementation and the challenges faced. Employing a systematic literature review, the study analyzes existing research on the IQF, identifying gaps and areas for further investigation. The findings reveal a need for more empirical research on the practical application of the IQF, particularly in relation to workplace learning and human resource development. The study suggests that future research should address the integration of the IQF with industry requirements and the impact of this framework on lifelong learning and career progression.